IMPLEMENTASI TEOREMA PHYTAGORAS DALAM PENYELESAIAN SOAL RANGKAIAN AC UNTUK MENINGKATKAN HASIL TES SISWA SMA - Elma Tri Istighfarini; Bambang Supriadi; Lailatul Nuraini; Ismanto Ismanto (JURNAL PEMBELAJARAN FISIKA, 2023)
Alternating current circuits are one of the physics taught in senior high school. Alternating current (AC) circuits are material related to mathematical equations so that to study this material students must have good mathematical abilities. This research will discuss the improvement of test results for AC circuit material, especially in the RL series, RC series, and RLC series using an alternative method in the form of the Pythagorean theorem on the impedance and voltage equations. This is because the Pythagorean theorem has a mathematical equation that is identical to the impedance and voltage equations in AC circuits. This research was conducted at SMAN 2 Jember using two classes, namely XII MIPA 5 and XII MIPA 7 classes. Based on the research that has been done, the result is an increase in test results in class XII MIPA 5 of 0.54 in the medium category and an increase in test results in class XII MIPA 7 of 0.30 in the medium category. Therefore student responses indicate that the Pythagorean theorem can attract students' interest, provide motivation with positive student responses and students are satisfied in applying it in solving AC circuit problems.